(untitled) (Papeles, 2021)
This article has as a central theme for reflection, the dignity of the person as the evaluative nucleus of the legal system at all levels of the legal framework known today, from this legal issue it is reflected on the scope and requirements arising from the dignity of the person with respect to the constitutional protection of the fundamental rights that emanate from said dignity. This analysis is complemented by means of the study of the recension of the dignity of the person at the level of the constitutions, to then go on to discuss in relation to the protection of the fundamental rights of vulnerable groups, in particular immigrants. For the development of the latter, the Spanish constitution was taken as the legal context as well as the doctrine emanating from the Constitutional Court of Spain, thus it was possible to clarify that in this country the legal system guarantees the foreigner a status of inherent rights to every person and inherent to human dignity.